Pharmacological characterization of levorphanol, a G-protein biased opioid analgesic - Le Rouzic, Valerie (Anesth Analg, 2019)
BACKGROUND: Levorphanol is a potent analgesic that has been used for decades. Most commonly used for acute and cancer pain, it also is effective against neuropathic pain. The recent appreciation of the importance of functional bias and the uncovering of multiple mu opioid receptor splice variants may help explain the variability of patient responses to different opioid drugs. METHODS: Here, we evaluate levorphanol in a variety of traditional in vitro receptor binding and functional assays. In vivo analgesia studies using the radiant heat tail flick assay explored the receptor selectivity of the responses through the use of knockout mice, selective antagonists and viral rescue approaches. RESULTS: Receptor binding studies revealed high levorphanol affinity for all the mu, delta and kappa opioid receptors. In (35)S-GTPγS binding assays, it was a full agonist at most mu receptor subtypes, with the exception of MOR-1O, but displayed little activity in β-arrestin2 recruitment assays, indicating a preference for G-protein transduction mechanisms. A knockout mouse and selective antagonists confirmed that levorphanol analgesia was mediated through classical mu receptors, but there was a contribution from 6TM targets, as illustrated by a lower response in an exon 11 knockout mouse and its rescue with a virally transfected 6TM receptor splice variant. Compared to morphine, levorphanol had less respiratory depression at equianalgesic doses. CONCLUSIONS: While levorphanol shares many of the same properties as the classic opioid morphine, it displays subtle differences that may prove helpful in its clinical use. Its G-protein signaling bias is consistent with its diminished respiratory depression while its incomplete cross-tolerance with morphine suggests it may prove valuable clinically with Opioid Rotation.